Using CiviCRM - Murray, Joseph; Murray, Joseph; Shaughnessy, Brian (Packt Publishing, 2011)
This book is a step-by-step tutorial with practical examples, introduced by a planning framework and illustrations of good relationship management techniques for a variety of situations. We begin with basics such as installation, low-level implementation, and CiviCRM's core modules before covering CiviCRM's advanced features and issues such as customization of CiviCRM and integrating it with Joomla! and Drupal. You should be able to quickly grasp and implement the basic elements of CiviCRM before moving on to the more advanced features and tools. This book is for project implementers, organization leaders, staff, and volunteers in advocacy, non-profit, and non-governmental organizations, elected officials, professional/trade associations, political campaigns and parties, government agencies, and other similar organizations who want to implement CiviCRM in a manner tailored to their organization's size, culture, and needs. It addresses CRM strategists, implementers, administrators, and end users looking to become power users in communicating, fundraising, managing events, memberships, grants, cases, and people-resource management.